Detecting Terrestrial Gamma-Ray Flashes with CubeSats: the scientific payload of the LIGHT-1 mission. Issue 1 (1st December 2022) - Di Giovanni, A; Arneodo, F.; Alkindi, L.; Benabderrahmane, M. L.; Mannino, M.; Oikonomou, P.; Kalos, S.; Torres, R.; Franchi, G.; Perillo, L.; Conicella, V.
Abstract: Terrestrial Gamma-ray Flashes (TGFs) are a prompt, high energy, very intense natural emission of gamma rays from Earth's atmosphere. Consisting of an upward sub-millisecond bursts of gamma rays (energy up to one hundred MeV), TGFs are mostly generated in powerful thunderstorms by lightnings. Given their production mechanism, several TGF counterparts can be detected too (mostly radio waves, electron beams and neutrons from photo-production). To investigate the X- and gamma-ray components, the ideal experiment is a space-borne instrument, operating at Low Earth Orbit (LEO) and featuring a fast detector response, possibly with spectral abilities. The CubeSat space mission LIGHT-1, launched in December 21st, 2021 and deployed from the International Space Station (ISS) on February 3rd, 2022, has been tailored around such physics requirements and it represents the technological demonstrator of possible larger missions to detect and localize TGF events. LIGHT-1 will help in making advancements in the TGF current knowledge: TGF occurring rates, average ignition altitude, production mechanism and effects on daily life on Earth are yet to be fully modeled and understood. In this paper the main characteristics of LIGHT-1 mission and the first preliminary flight data are reported.